Reducing the iron burden and improving survival in transfusion-dependent thalassemia patients: current perspectives - Bayanzay K; Alzoebie L (Journal of Blood Medicine, 2016)
Karim Bayanzay, Lama Alzoebie Department of Hematology, Gulf Medical University, Ajman, United Arab Emirates Abstract: Hypertransfusion regimens for thalassemic patients revolutionized the management of severe thalassemia; transforming a disease which previously led to early infant death into a chronic condition. The devastating effect of the accrued iron from chronic blood transfusions necessitates a more finely tuned approach to limit the complications of the disease, as well as its treatment. A comprehensive approach including carefully tailored transfusion protocol, continuous monitoring and assessment of total body iron levels, and iron chelation are currently the mainstay in treating iron overload. There are also indications for ancillary treatments, such as splenectomy and fetal hemoglobin induction. The main cause of death in iron overload continues to be related to cardiac complications. However, since the widespread use of iron chelation started in the 1970s, there has been a general improvement in survival in these patients. Keywords: hematology, chelators, deferoxamine, deferiserox, deferiprone, liver iron concentration, iron overload, serum ferritin concentration, hepatic iron storage, iron chelation therapy